Patterns of meat and vegetable consumption among community-dwelling adults aged 18 years and older in China - Deng, Xiaojing; Cheng, Hui; Wang, Wenjun; Hong, Yalin; Yuan, Xin; Xu, Huiqing; Xu, Yunting; Ao, Guofeng; Xu, Jian; Bian, Yeping; Ye, Qing (Frontiers in Nutrition, 2025)
BackgroundMeat and vegetable consumption was each vital for maintaining human health condition. Periodic surveillance and assessment of population-level meat and vegetable consumption are critically important for tailored healthy eating intervention. The primary aim of this study was to investigate the consumption patterns of meat and vegetables among community-dwelling adults in regional China in 2023.MethodsA cross-sectional survey was conducted in the first year of the post-COVID-19 pandemic in Nanjing Municipality of China. Participants were those residents aged 18 years or above and randomly selected from the whole municipality. The recommendations recently released by the China Nutrition Society in 2022 were used to assess participants’ meat and vegetable consumption level. Logistic regression models were used to identify potential influencing factors of meat and vegetable consumption.ResultsAmong the 60,945 participants analyzed, the medians of meat and vegetable consumption were 700.0 g/wk (interquartile range = 375.0, 1,100) and 200.0 g/d (interquartile range = 100.0, 300.0), respectively. Moreover, 13.7% (95%CI = 13.4, 13.9), 18.1% (95%CI = 17.8, 18.5), and 68.2% (95%CI = 67.8, 68.6) of participants consumed meat under, within, and beyond the recommended level, respectively, whereas 71.1% (95%CI = 70.7, 71.4) and 28.9% (95%CI = 28.6, 29.3) consumed vegetables under and reaching the recommended level, respectively. Selected socio-demographic characteristics, lifestyle and behaviors, and chronic conditions were associated with meat and vegetable consumption.ConclusionA large proportion of community-dwelling adults consumed meat exceeding the recommended level, whereas a small proportion consumed vegetables reaching the recommended level in regional China in 2023. Moreover, disparities of meat and vegetable consumption existed in socio-demographic characteristics, lifestyle and behaviors, and selected chronic conditions. However, no causality could be inferred due to the nature of the cross-sectional study. For future tailored population-level interventions of healthy eating of meat and vegetables, particular attention should be paid to participants’ socio-demographic characteristics, lifestyle and behaviors, and specific chronic conditions.